An empirical examination of leadership styles' impact on innovative behaviour and entrepreneurial orientation in Canadian firms: a cross-cultural perspective. (9th August 2019) - Gross, Raushan; Cabanda, Emilyn
In the small and medium-sized enterprise, cross-cultural and entrepreneurial leadership research, there has been an assumption that one's leadership style modus operandi is one size fits all. In the current research, Canadian leadership styles and leadership differences between Canadian and North American business entrepreneurial leaders were tested. New empirical results are substantive and add to the cross-culture entrepreneurial theory. There are limited Canadian-based entrepreneurial studies: the expected corollary was that there were no differences between Canadian and American leadership styles; however, the results reported otherwise. Data were obtained from 145 Canadian respondents located in Toronto, Ontario in Canada. Data were analysed with hierarchical regression analyses and multivariate analysis of variance in testing seven hypotheses. The analyses reported a statistically significant difference in Canadian and North American leadership styles employed in an entrepreneurial context.